(untitled) (Journal of the College of Basic Education, 2023)
Students of the College of Basic Education are prepared as teachers for primary schools, so there is importance to studying their needs, including psychological security, because it affects their behavior and direction.The current research aims to identify the level of these students’ sense of psychological security, and whether there are significant differences according to the variables of gender, stage, and specialization. The data were processed using the t-test, the Cowder-Richardson equation, the binary correlation coefficient, and the triple analysis of variance, and the results revealed a tendency (70%) of the research sample to lack a sense of psychological security, and there were no significant differences in psychological security according to the research variables. The research included some recommendations and suggestions based on the results.